2021
DOI: 10.1177/00207640211001893
|View full text |Cite
|
Sign up to set email alerts
|

‘Modelling social exclusion in a diagnostically-mixed sample of people with severe mental illness’

Abstract: Background: Social inclusion is an important indicator of recovery in individuals with severe mental illness. The Social Inclusion Questionnaire User Experience (SInQUE) is a new measure of social inclusion for mental health service users which assesses five domains (consumption, production, access to services, social integration and civil engagement). It has good psychometric properties and is acceptable to service users and mental health professionals. It is not clear whether individuals with different diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Social exclusion can be conceptualized as both a cause and a consequence of mental illness [ 12 ]. Furthermore, greater social inclusion is associated with better quality of life and lower levels of loneliness among those with severe mental illness, suggesting that social exclusion is an important area for mental health practitioners to try to address [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social exclusion can be conceptualized as both a cause and a consequence of mental illness [ 12 ]. Furthermore, greater social inclusion is associated with better quality of life and lower levels of loneliness among those with severe mental illness, suggesting that social exclusion is an important area for mental health practitioners to try to address [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, stakeholder feedback from a previous study testing the SInQUE indicated that the measure may be useful in clinical practice to assess social inclusion, facilitate important conversations with service users, and guide care and support planning [ 34 ]. Furthermore, a consistent research recommendation from the developers of the SInQUE tool has been to investigate whether the measure has utility as a care-planning tool to promote social inclusion in routine mental health practice [ 13 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a consistent research recommendation from the developers of the SInQUE tool has been to investigate whether the measure has utility as a care planning tool, to promote social inclusion in routine mental health practice [13,34].…”
Section: Introductionmentioning
confidence: 99%
“…Social exclusion can be conceptualized as both a cause and a consequence of mental ill-health [12]. Furthermore, greater social inclusion is associated with better quality of life and lower levels of loneliness among those with severe mental illness, suggesting that social exclusion is an important area for mental health practitioners to try to address [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation